Outcome of transcatheter atrial septal defect closure in a nationwide cohort - Muroke Valtteri; Jalanko Mahir; Haukka Jari; Hartikainen Jarmo; Tahvanainen Antti; Ukkonen Heidi; Ylitalo Kari; Pihkala Jeanene; Sinisalo Juha (TAYLOR & FRANCIS LTD, 2025)
Background: Transcatheter (TC) atrial septal defect (ASD) closure has been the mainstay of therapy for secundum-type ASDs for over 20 years.
Aims: This nationwide cohort evaluated the long-term outcome of transcatheter-closed ASDs.
Methods: The study enrolled every transcatheter ASD closure performed in Finland from 1999 to 2019. Five age, sex, and municipality-matched controls per ASD patient were gathered from the general population. The median follow-up period was 5.9 years (range 0-20.8). We used the hospital discharge register to gather all hospital visits and diagnoses. Closure complications and echocardiographic changes were collected from the electronic health records.
Results: Transcatheter ASD closure was performed in 1000 patients (68.5% females) during the study period. The median (range) age at the time of the procedure was 37.9 (1.8-87.5) years. ASD patients had an increased risk for new-onset atrial fibrillation (RR 2.45, 95% CI: 1.84-3.25), migraine (RR 3.61, 95% CI: 2.54-5.14), ischemic heart disease (RR 1.73, 95% CI: 1.23-2.45), ventricular fibrillation/tachycardia (RR 3.54 (95% CI: 1.48-8.43) and AV conduction disorder (RR 3.60, 95% CI: 1.94-6.70) compared to the control cohort. Stroke risk was not increased (RR 1.36, 95% CI: 0.91-2.03). Adverse events occurred in 6.3% (n = 63) of the patients, including four erosions and ten device embolizations.
Conclusion: After TC closure of ASD, patients had a higher risk of new-onset atrial fibrillation and migraine than controls without ASD. As novel findings, we found an increased risk for ischemic heart disease, AV conduction disorders, and ventricular fibrillation/tachycardia.Key messagesEven though patients have an excellent overall prognosis after percutaneous ASD closure, the increased incidence of major comorbidities like atrial fibrillation and heart failure prompts more thorough lifelong follow-up.This study's novel findings revealed the increased risk for ischemic heart disease, AV conduction disorders, or ventricular tachycardia/fibrillation during the follow-up.Major complications after the closure are rare; erosion is seen in 0.4% of the patients and embolization in 1.0% of the patients.